2020
DOI: 10.1128/mbio.00095-20
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Cell Surface Glycosidases and Glycan-Binding Proteins Dictates the Utilization of Specific Beta(1,3)-Glucans by Human Gut Bacteroides

Abstract: The human gut microbiota (HGM) has far-reaching impacts on human health and nutrition, which are fueled primarily by the metabolism of otherwise indigestible complex carbohydrates commonly known as dietary fiber. However, the molecular basis of the ability of individual taxa of the HGM to address specific dietary glycan structures remains largely unclear. In particular, the utilization of β(1,3)-glucans, which are widespread in the human diet as yeast, seaweed, and plant cell walls, had not previously been res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(127 citation statements)
references
References 98 publications
2
125
0
Order By: Relevance
“…4). For Bacteroides species belonging to the HGM, the GH16 enzymes that have been characterised so far include specificities towards porphyran, agarose, β-1,3-glucan, and mixed linkage glucan [24][25][26][27] . The genetic loci encoding the GH16 enzymes upregulated on mucin also contain genes encoding SusCD pairs for the Bacteroides spp.…”
Section: Resultsmentioning
confidence: 99%
“…4). For Bacteroides species belonging to the HGM, the GH16 enzymes that have been characterised so far include specificities towards porphyran, agarose, β-1,3-glucan, and mixed linkage glucan [24][25][26][27] . The genetic loci encoding the GH16 enzymes upregulated on mucin also contain genes encoding SusCD pairs for the Bacteroides spp.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming the importance of three GHs (GH3, GH16 and GH158) associated with PUL36 and one GH (GH30_3) of PUL21 for degrading laminarin, these enzymes were cloned and heterologous expressed in E. coli . While we were working on these enzymes, the study of Dejean et al (2020) 52 appeared in which they characterized Bu GH3, Bu GH16, and Bu GH158. Therefore in the study, we mainly focused to work with Bu GH158, which is not identical to one that characterized (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S7) and Bu GH158 ( Figure 4(b -d)) indicated that both enzymes can produce oligosaccharides, which can be utilized by other bacteria present in their vicinity. 52 Especially, such cooperativity is rarely seen with Gram-positive bacteria. In order to check this hypothesis, Gram-positive bacteria were spotted near to B. uniformis JCM 13288 T on agar plate and subsequently, CFUs were calculated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations